Genome‐inferred spatio‐temporal resolution of an uncultivated Roizmanbacterium reveals its ecological preferences in groundwater - Patricia Geesink; Carl‐Eric Wegner; Alexander J. Probst; Martina Herrmann; Hang T. Dam; Anne‐Kristin Kaster; Kirsten Küsel (Environmental Microbiology, 2020)
Summary Subsurface ecosystems like groundwater harbour diverse microbial communities, including small‐sized, putatively symbiotic organisms of the Candidate Phyla Radiation, yet little is known about their ecological preferences and potential microbial partners. Here, we investigated a member of the superphylum Microgenomates ( Cand . Roizmanbacterium ADI133) from oligotrophic groundwater using mini‐metagenomics and monitored its spatio‐temporal distribution using 16S rRNA gene analyses. A Roizmanbacteria‐specific quantitative PCR assay allowed us to track its abundance over the course of 1 year within eight groundwater wells along a 5.4 km hillslope transect, where Roizmanbacteria reached maximum relative abundances of 2.3%. In‐depth genomic analyses suggested that Cand . Roizmanbacterium ADI133 is a lactic acid fermenter, potentially able to utilize a range of complex carbon substrates, including cellulose. We hypothesize that it attaches to host cells using a trimeric autotransporter adhesin and inhibits their cell wall biosynthesis using a toxin–antitoxin system. Network analyses based on correlating Cand . Roizmanbacterium ADI133 abundances with amplicon sequencing‐derived microbial community profiles suggested one potential host organism, classified as a member of the class Thermodesulfovibrionia (Nitrospirae). By providing lactate as an electron donor Cand . Roizmanbacterium ADI133 potentially mediates the transfer of carbon to other microorganisms and thereby is an important connector in the microbial community.